(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article argues that the complex, changing and uncertainties of the modern era demand new thinking and qualities from young people. The author scientifically substantiates the development of the quality of tolerance of youth to uncertainties and the great importance of complex thinking in this process.